Persepsi Pustakawan Terhadap Diklat Daring (Studi Kasus Pustakawan PDDI-LIPI Peserta Diklat in Passing Pustakawan) - Juni Karichnarsi; Rulina Rachmawati (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2022)
This research was aimed to study librarians’ perceptions towards online library training during the COVID-19 pandemic. This study used a descriptive-qualitative and a triangulation method. A survey was conducted on eight librarians of PDDI-LIPI who had joined an in passing online librarian training via Eldika, a web-based application program developed by the National Library. The recorded perceptions were perceptions towards trainers, learning media/ platform, learning materials, and online training. The results were summarized into tables and narrative descriptions, then triangulated through direct interviews to explore the causes and solutions to problems related to the online training. The result of this research indicated that librarians’ perceptions towards all four online training indicators were positive. However, weakness was found regarding the online training platform. Based on the findings, this study suggested that the National Library and other institutions provide online librarian training to develop some more friendly platforms accessible for librarians with various IT skills, and an IT support service quickly responded during training.